Mitochondrial assembly receptor expression is an independent prognosticator for patients with oral tongue squamous cell carcinoma. (July 2017) - Su, Yan-Ye; Chen, Chang-Han; Chien, Chih-Yen; Lin, Wei-Che; Huang, Wan-Ting; Li, Shau-Hsuan
Introduction: Recent evidence suggests that the local renin-angiotensin system has been implicated in various malignancies. The mitochondrial assembly receptor is a newly identified receptor for angiotensin peptides, angiotensin-(1-7), and has an important role in the renin-angiotensin system. However, the role of the mitochondrial assembly receptor in the prognosis of cancer patients remains unclear. The aim of this study was to evaluate the significance of mitochondrial assembly receptor signaling in the prognosis of oral tongue squamous cell carcinoma. Methods: Mitochondrial assembly receptor immunohistochemistry was examined in 151 oral tongue squamous cell carcinoma patients and was correlated with treatment outcome. The functional relevance of the mitochondrial assembly receptor in oral tongue squamous cell carcinoma cell lines was evaluated by 3-(4, 5-dimethylthiazole-2-yl)-2, 5-diphenyltetrazolium bromide reduction and bromodeoxyuridine incorporation assays. Results: Mitochondrial assembly receptor overexpression was significantly correlated with early pathological T classification ( p =0.029) and the absence of extracapsular spread ( p =0.039). Univariate analyses demonstrated that mitochondrial assembly receptor overexpression was significantly associated with superior overall survival ( p =0.012). In multivariate comparison, mitochondrial assembly receptor overexpression remained independently associated with superior overall survival ( p =0.008, hazard ratio=1.862). In vitro, angiotensin-(1-7) suppressed the cell growth in oral tongue squamous cell carcinoma cells, and this response was reversed by the mitochondrial assembly receptor antagonist, A779. Conclusion: Mitochondrial assembly receptor expression is independently associated with the prognosis of oral tongue squamous cell carcinoma patients. These findings suggest that mitochondrial assembly receptor signaling may be a promising novel target for oral tongue squamous cell carcinoma.